Development of Project-Based Learning Oriented Student Worksheets to Improve Students' Creative Thinking Skills on Class X High School Nanotechnology Material - Kusumawati Dwiningsih; Nabiilah Aisy (Jurnal Penelitian Pendidikan IPA, 2024)
The purpose of this study is to determine: the feasibility of project-based learning-oriented student worksheets in terms of content validity and construct validity, and the effectiveness of   project-based learning-oriented student worksheets in terms of increasing students' creative thinking skills. Development of Project-Based Learning oriented student worksheets to improve students' creative thinking skills on class X high school nanotechnology material using the Research and Development (R&D) method with a 4D development model (Define, Design, Develop, and Disseminate). However, this research was carried out only until the third stage, namely Develop. The results of data analysis and discussion are as follows: the worksheets of project-based learning-oriented students developed are declared to have met the eligibility requirements in terms of content validity and construct validity with mode (Mo) values ≥ 4 and R ≥ 75%, and student worksheets project-oriented based learning developed was declared effective in terms of increasing students' creative thinking ability with a percentage of N-Gain of 79% moderate category (0.30-0.70) and 21% high category (0.7-1). Thus, Project Based Learning Oriented Student Worksheets can be used to improve students' creative thinking skills on Nanotechnology material.